Role of Glucan and Surface Protein BAD1 in Complement Activation by Blastomyces dermatitidis Yeast - Zhang, Mason X. (American Society for Microbiology, 2001)
Our previous studies showed that Blastomyces dermatitidis yeast activates the human complement system, leading to deposition of opsonic complement fragments onto the yeast surface. This report examines the influence of altered surface expression of glucan or BAD1 protein (formerly WI-1) on the yeast's ability to activate and bind C3. Compared to the wild type, a glucan-deficient mutant yeast delayed initiation of C3 deposition and reduced C3-binding capacity by 50%. Linkage of baker's-yeast β-glucan to the glucan-deficient yeast restored initial C3 deposition kinetics to the wild-type level and partially restored C3-binding capacity, suggesting that β-glucan is an initiator of complement activation and a C3 acceptor. The role of BAD1 in B. dermatitidis yeast-complement interaction was also assessed. BAD1 knockout yeast initiated faster C3 deposition and increased C3-binding capacity compared to the wild-type yeast or a BAD1-reconstituted yeast, suggesting either a lack of an intrinsic ability in BAD1 or an inhibitory role of BAD1 in complement activation and binding. However, both complement activation and the capacity for C3 binding by the wild-type yeast were enhanced in normal human serum supplemented with an anti-BAD1 monoclonal antibody (MAb) or in immune sera from blastomycosis patients. Microscopic analysis revealed that more initial C3-binding sites were formed on yeast in the presence of both naturally occurring complement initiators and exogenous anti-BAD1 MAb, suggesting that anti-BAD1 antibody enhanced the ability of B. dermatitidis yeast to interact with the host complement system. Thus, glucan and BAD1 have distinctly different regulatory effects on complement activation by B. dermatitidis.